Crafting Collective Management Institutions in Messy Real-World Settings: A Call for Action Research. Issue 1 (1st March 2022) - Sinner, Jim; Tadaki, Marc; Challies, Edward; Kilvington, Margaret; Tane, Paratene; Robb, Christina A.
There is considerable interest in collective management as a potential solution to complex environmental problems, but existing research offers little guidance for the messy real-world task of creating new institutions. Research on collective management of the commons has mostly analyzed institutions that already exist, in order to derive and test general design principles to illuminate what makes institutions successful. While such principles are useful, we want to provide guidance to those who are crafting new institutions in contexts that do not conform neatly to these design principles, and to inform this crafting with insights about environmental subjectivity and social justice. We report on a study from New Zealand that applies an action research orientation, involving four case study catchments where farming and indigenous leaders are in dialogue about emerging collective institutions to address declining health of freshwater systems and other shared concerns. We show how these institutional crafters considered, challenged and stretched the general design principles as they assessed the principles' relevance to their cases, which involve externalities from diffuse pollution and hence are a less-than-straightforward collective management problem. In this dialogue, catchment leaders shared different perspectives, including concepts from indigenous culture, and explored what these mean for their own identities and motivations as farmers and environmental stewards. The dialogue has created conditions in which farmers and indigenous leaders interact as peers and partners in the enterprise of institution-building, providing an opportunity to address issues of social justice as well as environmental sustainability. We argue that commons research can benefit from (i) a theoretical agenda that reorients inquiry to practical issues of crafting institutions as well as (ii) a methodological agenda involving action research as a way of recognizing and working through complexity, while also working in partnership with local actors to achieve change on the ground.